Effects of Nitrogen and Zinc Fertilizers on Grain Yield and Some Yield Components of Pehlivan - Tas, Birol; Celik, Necmettin (Asian Journal of Chemistry, 2010)
This research was performed to determine the effect of which wheat will have on yield and some yield components by applying two importants elements of which many researchers investigated only one of them (only N or only Zn). It was carried out on experimental areas of Uludag University Agricultural Faculty where Zn deficiency was present. As an experimental material, Pehlivan, an important bread wheat, was used for two cultivation periods. The experiment area was established in a randomized design with three replicates on 1.2 × 5 m = 6 m2. In this experiment, five different zinc doses (Z0: 0 g da-1, Z1:100 g da-1, Z2:150 g da-1, Z3:200 g da-1, Z4: 250 g da-1) and four different nitrogen doses (N0: 0 kg da-1, N5: 5 kg da-1, N10: 10 kg da-1, N15: 15 kg da-1) were applied. As a result, it was determined that Zn is of no significant effect on plant height, seed number pers pike, 1000-seed weight and yield. However, extremely positive results were obtained in combinations in which Zn forms with nitrogen. The best results in terms of plant height were obtained in Zn2N3, seed number per spike in Zn3N10, 1000-seed weight in Zn0N15, respectively. As to yield, average Z3N10, Z3N10, Z4N5, Z4N10 and Z4N15 combinations were over 700 kg da-1.